2022
DOI: 10.1002/pbc.30089
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell disease and social determinants of health: A scoping review

Abstract: Social determinants of health (SDoH) may impact outcomes in sickle cell disease (SCD). We conducted a comprehensive literature review of five electronic databases to elucidate the relationship between SDoH and SCD, and identify gaps in the literature. Our search yielded 59 articles, which we organized into five SDoH areas: Neighborhood and Built Environment, Health and Healthcare, Social and Community Context, Education, and Economic Stability. We found that social determinants, such as access to healthcare, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 82 publications
1
24
0
2
Order By: Relevance
“… 1 12 The current literature also suggests that children with SCD predominantly belong to families of lower socioeconomic status (SES) and parents with lower educational attainment, 12 a social determinant of health (SDoH). 13 Furthermore, studies have shown considerably higher healthcare usage among children with SCD from low SES families, whose SES status directly affects the timeliness and quality of treatment. 12 Additional documented barriers to care include lack of access to healthcare facilities, lack of knowledge about SCD, limited SCD management options; or denial of care by specialised health facilities due to having a healthcare plan with lower reimbursement rates.…”
Section: Introductionmentioning
confidence: 99%
“… 1 12 The current literature also suggests that children with SCD predominantly belong to families of lower socioeconomic status (SES) and parents with lower educational attainment, 12 a social determinant of health (SDoH). 13 Furthermore, studies have shown considerably higher healthcare usage among children with SCD from low SES families, whose SES status directly affects the timeliness and quality of treatment. 12 Additional documented barriers to care include lack of access to healthcare facilities, lack of knowledge about SCD, limited SCD management options; or denial of care by specialised health facilities due to having a healthcare plan with lower reimbursement rates.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with SCD experience greater rates of poverty and fewer protective SES factors when compared with the Black/African American population in the United States 10,11 . Patients from the most disadvantaged environments are at increased risk for poor health‐related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For pediatric patients with sickle cell disease (SCD), an inherited hemoglobinopathy predominantly seen among individuals of African descent in the United States, the dual burden of living with a chronic disease and racial inequity increases this population's vulnerability to social disparities 7 . Environmentally, patients with SCD experience greater rates of poverty and fewer protective socioeconomic factors when compared with the Black/African American population in the United States 10,11 . Patients from the most disadvantaged environments experience reduced health‐related quality of life 12 and are at higher risk for in‐hospital mortality 13 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations